A very rare presentation of lung cancer: Metastases to the distal phalanx of index–case report - Afrăsânie, Vlad-Adrian (Medicine (Baltimore), 2019)
RATIONALE: Acrometastases of the hand are an unusual sign of lung cancer onset and may often be mistaken for other benign disorders, thus delaying diagnosis and treatment. PATIENT CONCERNS: A 58-year-old man presented at the Rheumatology Clinic with a lump in the distal phalanx of the right index finger associated with intense pain, swelling, rib pain, and hemoptysis. DIAGNOSES: Given the clinical manifestations, an x-ray of the right hand was performed, and it revealed an osteolytic lesion in the distal phalanx of the right index finger. The subsequent CT of the thorax and abdomen showed a lung tumor, osteolytic lesions in the ribs, sternum, and the thoracic spine. INTERVENTIONS: Amputation of the phalanx was decided on account of intense pain refractory to NSAIDs and opioids. Pathology assessment established the diagnosis of bone metastases secondary to lung adenocarcinoma. The patient underwent 6 cycles of first-line palliative chemotherapy with cisplatin and gemcitabine with partial response according to the RECIST 1.1. criteria. EGFR and ALK testing were not available at the time. A year later, the patient presented with progressive disease, which lead to 6 more cycles of chemotherapy with docetaxel. The disease progressed during chemotherapy and the patient was switched to erlotinib. OUTCOMES: After 7 months of anti-EGFR treatment, the patient passed away due to disease progression, thus having an overall survival of 25 months. LESSONS: On rare occasions, acrometastases of the hand may be the first manifestation of a lung cancer and, as such, they must be taken into consideration in the differential diagnosis of rheumatologic disorders. They are a poor prognosis marker, but some cases like this one can have a better survival than reported in the literature, most likely due to that particular cancer's biology.